2014
DOI: 10.5539/ijef.v6n4p110
|View full text |Cite
|
Sign up to set email alerts
|

Farmers Characteristics and Its Influencing on Loans Resettlement Decision in Sri Lanka

Abstract: This study investigates the impact of socio-economic characteristics of the farmers and its impact on their loans resettlement behavior in the People's Bank, Puttalam branch in Sri Lanka. Secondary data were collected from the bank officials and the data were analyzed with 100 applicants who are cultivating paddy as a major crop and other field crops during the Maha and Yala season 2011/2012. This study was analyzed using descriptive statistics, Tobit model and in addition to that elasticity of the loan repaym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The types of variables used in the literature on credit scoring for farmers mainly describe financial ratios such as liquidity, profitability and leverage (Durguner and Katchova 2007;Jouault and Featherstone 2011;Ziari et al 1995); farmer characteristics (educational level, age, goods, etc;Limsombunchai et al (2005)); farm characteristics, such as types of crops and farm size (Limsombunchai et al 2005;Miller and LaDue 1988;Novak and LaDue 1999;Onyenucheya and Ukoha 2007); and credit features, including credit history (Aruppillai and Phillip 2014;Eyo and Ofem 2014;Hou et al 2005;Jouault and Featherstone 2011). Other studies have used weather data (Pelka et al 2015;Römer et al 2017) and variables related to the sustainability of crops (Henning and Jordaan 2016).…”
Section: Measuring Credit Risk In the Agribusiness Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…The types of variables used in the literature on credit scoring for farmers mainly describe financial ratios such as liquidity, profitability and leverage (Durguner and Katchova 2007;Jouault and Featherstone 2011;Ziari et al 1995); farmer characteristics (educational level, age, goods, etc;Limsombunchai et al (2005)); farm characteristics, such as types of crops and farm size (Limsombunchai et al 2005;Miller and LaDue 1988;Novak and LaDue 1999;Onyenucheya and Ukoha 2007); and credit features, including credit history (Aruppillai and Phillip 2014;Eyo and Ofem 2014;Hou et al 2005;Jouault and Featherstone 2011). Other studies have used weather data (Pelka et al 2015;Römer et al 2017) and variables related to the sustainability of crops (Henning and Jordaan 2016).…”
Section: Measuring Credit Risk In the Agribusiness Sectormentioning
confidence: 99%
“…Limsombunchai et al (2005) defined the lending decision as a function of borrower characteristics, relationship indicators and dummy variables about the agricultural sector and loan information. Aruppillai and Phillip (2014) showed that considering socioeconomic characteristics, such as number of family members, amount of loan disbursement and secondary education, improves the efficiency of the lending decision.…”
Section: Introductionmentioning
confidence: 99%